Tinjauan Yuridis Terhadap Sengketa Merek GoTo dan GOTO Pada Putusan Nomor 71/PDT.SUS-HKI/MEREK/2021/PN NIAGA JKT.PST dengan Prinsip Iktikad Baik (Good Faith) Dalam Pendaftaran Merek - Monica, Maria Christina; Gunawan, Yusuf (Neolectura, 2024)
This study aims to examine the Legal Review of the Case Dispute filed by PT. Terbit Financial Technology against two large companies, namely PT. Tokopedia and PT. Aplikasi Karya Anak Bangsa or known as Gojek. Case with case number 71/Pdt.Sus- HKI/Merek/2021/PN.Niaga.Jkt.Pst. The research method used is Qualitative with a normative legal approach, literature and literature studies and a case law approach. The discussion that will be analyzed in this study is related to the regulations regarding the rejection of trademark registration in the Trademark and Geographical Indications Law Number 20 of 2016 which regulates the procedures, criteria, and reasons for rejection of trademark registration, including the considerations used by the Directorate General of Intellectual Property in rejecting a trademark. The researcher provides an explanation of the legal consequences arising from the rejection of the trademark, both for the rejected applicant and third parties who have an interest in the trademark. The legal consequences can be in the form of implications for the applicant in the form of legal efforts that can be taken, such as filing objections or lawsuits, as well as impacts on the rights to other brands related to the dispute. The results of this study indicate that the application of the principle of good faith means ensuring that the use of a name or term is carried out with full awareness of the context, respecting the intellectual property rights of others, and communicating openly with all relevant stakeholders. Thus, the company or parties involved can minimize the potential for conflict and build a strong reputation based on integrity and honesty.